Building a Thermal Shutdown Cathode for Li‐Ion Batteries Using Temperature‐Responsive Poly(3‐Dodecylthiophene). Issue 7 (5th June 2020) - Li, Hui; Zhang, Xinnuo; Zhang, Chongrong; Cao, Yuliang; Yang, Hanxi; Ai, Xinping; Zhong, Faping
Abstract : Thermal shutdown electrodes can provide a safety control for lithium‐ion batteries (LIBs) under a wide range of applications. However, developing such an electrode is difficult due to the lack of electrochemically compatible materials with suitable temperature‐responsive functions. Herein, a new thermal‐responsive conductive polymer—poly(3‐dodecylthiophene) (P3DDT)—is reported, and this polymer is used as a coating layer of electrode substrate to fabricate a thermal shutdown cathode of Al/P3DDT/LiCoO2 (LCO‐P3DDT). Benefited by the high room‐temperature conductivity, strong positive‐temperature‐coefficient (PTC) effect, and appropriate transition temperature of the P3DDT layer, the LCO‐P3DDT cathode not only exhibits similar electrochemical performance as a conventional LCO cathode at normal operating temperatures, but also plays a desired shutdown function to switch off the electrode reaction at elevated temperatures of ≥90 °C, thus protecting the cell from thermal runaway. This PTC effect of p‐doped P3DDT is found to be given rise by the thermal de‐doping of anions from the doped P3DDT skeleton at elevated temperature. This temperature‐responsive mechanism may provide a new insight for designing better thermal shutdown electrodes for a wide variety of battery applications. Abstract : A thermal shutdown cathode is fabricated by sandwiching a temperature‐responsive poly(3‐dodecylthiophene) (P3DDT) layer between a cathode substrate and electrode active layer. Benefiting from the strong positive‐temperature‐coefficient (PTC) effect of the P3DDT layer, such a cathode can provide effective thermal protection for Li‐ion cells at risky temperatures.